Synthesis of nanomaterials using various top-down and bottom-up approaches, influencing factors, advantages, and disadvantages: A review - Abid, Namra; Khan, Aqib Muhammad; Shujait, Sara; Chaudhary, Kainat; Ikram, Muhammad; Imran, Muhammad; Haider, Junaid; Khan, Maaz; Khan, Qasim; Maqbool, Muhammad (Advances in colloid and interface science, 2022)
Nanotechnology is one of the emerging fields of the 21st Century. Many new devices and patentable technology is based on nanomaterials (NMs). One of the dominant factors in the use of nanomaterials and their applications in various fields is the synthesis and growth mechanism of nanostructures and nanomaterials. A nanostructured material may have been a good candidate in one application but could be more useful in a different application if synthesized by a different mechanism and technique. Similarly, the structure and morphology of a nanomaterial also depend upon the method of growth and synthesis. For example, it is easy to grow and synthesize amorphous nanostructured thin film using the plasma magnetron sputtering technique, but it may be difficult to obtain a similar structure using the thermal evaporation process due to the nature of the technique itself. In this study, the Top-down and Bottom-up methods and techniques of synthesizing nanostructured materials are reviewed, compared, and analyzed. Both approaches are critically analyzed, and the influencing factors on the synthesis of different nanomaterials, the advantages, and disadvantages of each technique are reported. This review also provides a step-by-step analysis of the choice of method for the synthesis of namomaterials for specific applications. [Display omitted] •The Top-down and Bottom-up methods and techniques of synthesizing nanostructured materials.•Application oriented advantages and disadvantages of each synthesis and fabrication technique.•Factors affecting the synthesis and fabrication of nanomaterials in each technique.•Critical analysis and suitability of nanomaterials in various applications.